Combined Analytical-Numerical Solution for MHD Viscous Flow over a Stretching Sheet. (13th March 2014) - Mabood, Fazle; Khan, Waqar A.
Abstract : We studied the two-dimensional flow of viscous and electrically conducting fluid over a stretching sheet under the influence of constant magnetic field. Approximate analytical solution of governing nonlinear boundary layer equation via optimal homotopy asymptotic method (OHAM) is obtained. For numerical comparison we used Runge-Kutta-Fehlberg fourth-fifth-order method. The effect of different parameters on fluid flow is analyzed. It is found that the OHAM solution is very close to the numerical solution for different assigned values of parameters; this thus indicates the feasibility of the proposed method (OHAM).